Indeks Ketahanan Lingkungan sebagai Bukti Pembuatan Kebijakan: Sebuah Sosialisasi Evidence-based Policy di Desa Lorok, Kecamatan Indralaya Utara, Kabupaten Ogan Ilir - Faisal Nomaini; Muhammad Husni Thamrin; Oemar Madri Bafadhal (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Practitioners and academics are faced with problems about why public policy fails to achieve its goals and is met with resistance from the public. This then led to the birth of an evidence-based policy (EBP) concept that is trusted and has been proven to increase policy success. Unfortunately, this concept has not yet reached the village government level. Therefore, this community service aims to socialize this concept and put it into practice by taking a case study on the environmental resilience index as one of the compilations of the village developing index (IDM). We took a case study in Desa Lorok, Kecamatan Indralaya Utara, Kabupaten Ogan Ilir for several reasons, such as governance and their readiness to accept this new concept. This community service is a model for implementing EBP by the needs and characteristics of the community because it is formulated jointly between us as academics and the community. Another result is policy recommendations for increasing environmental resilience by focusing on the criteria composing the index.